2015
DOI: 10.4137/tog.s29652
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Metabolism and Oncogenic Process: Role of microRNAs

Abstract: Cancer is a complex disease that arises from the alterations in the composition and regulation of several genes leading to the disturbances in signaling pathways, resulting in the dysregulation of cell proliferation and death as well as the ability of transformed cells to invade the host tissue and metastasize. It is increasingly becoming clear that metabolic reprograming plays a critical role in tumorigenesis and metastasis. Therefore, targeting this phenotype is considered as a promising approach for the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 220 publications
(224 reference statements)
0
22
0
Order By: Relevance
“…A number of cancer associated mutations affect metabolism and defects in mitochondria are seen in cancer that also link metabolism with cancer initiation and progression. Recent studies have shown that changes in cellular metabolism can alter the expression of specific microRNAs and promote epigenetic changes in tumor cells (Arora et al, 2015; Bishop and Ferguson, 2015; Chan et al, 2015). Although some of these interactions are mentioned above, in-depth discussions of all of the interactions that occur between cancer and metabolism are beyond the scope of this review and the reader is referred to a number of reviews on these subjects (Gatenby and Gillies, 2004; Vander Heiden et al, 2009; Cantor and Sabatini, 2012; Ward and Thompson, 2012; Semenza, 2013; Gaude and Frezza, 2014; Masson and Ratcliffe, 2014; Boroughs and DeBerardinis, 2015; Casey et al, 2015; Robey et al, 2015; Asati et al, 2016; Barron et al, 2016; Bost et al, 2016; Molon et al, 2016; Pavlova and Thompson, 2016; Pérez-Escuredo et al, 2016).…”
Section: Tumor Metabolismmentioning
confidence: 99%
“…A number of cancer associated mutations affect metabolism and defects in mitochondria are seen in cancer that also link metabolism with cancer initiation and progression. Recent studies have shown that changes in cellular metabolism can alter the expression of specific microRNAs and promote epigenetic changes in tumor cells (Arora et al, 2015; Bishop and Ferguson, 2015; Chan et al, 2015). Although some of these interactions are mentioned above, in-depth discussions of all of the interactions that occur between cancer and metabolism are beyond the scope of this review and the reader is referred to a number of reviews on these subjects (Gatenby and Gillies, 2004; Vander Heiden et al, 2009; Cantor and Sabatini, 2012; Ward and Thompson, 2012; Semenza, 2013; Gaude and Frezza, 2014; Masson and Ratcliffe, 2014; Boroughs and DeBerardinis, 2015; Casey et al, 2015; Robey et al, 2015; Asati et al, 2016; Barron et al, 2016; Bost et al, 2016; Molon et al, 2016; Pavlova and Thompson, 2016; Pérez-Escuredo et al, 2016).…”
Section: Tumor Metabolismmentioning
confidence: 99%
“…This metabolic shift contributes to excess glycolytic flux, lactate, low pH, activation of oncogenes and suppression of tumor suppressor genes. Glycolytic switch in cancer cells together with tumor secreted growth factors and TME drives angiogenesis in tumors by reprogramming EC metabolism and angiogenic signaling in EC [173,174]. miRNA which are angiogenic also participate in the regulation of EC metabolism.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…MiRs are involved in the regulation of cell development, differentiation, proliferation, and apoptosis, and are closely related to the occurrence and development of many diseases [22]. MiR-21 is an oncogenic miR in human malignant tumors, and it is the only miR known to be highly expressed in almost all solid tumors [23, 24].…”
Section: Discussionmentioning
confidence: 99%